The Quality of Family Life and its Relationship to Psychological Stress for Children with Hearing Disabilities - AlQaaydeh, Muhammad; El-Zraigat, Ibrahim (Dirasat: Educational Sciences, 2022)
The present study aims to identify the quality of family life and its relationship to psychological stress for children with hearing disabilities from the point of view of their parents in Jordan. The study included 100 parents of students with hearing disability. The paricipants were selected using a convenient method. The researchers constructed two scales, namely the scale of quality of family life and the scale of psychological stress. The validity and reliability indications of the two measures were acheived. The results indicated that family interaction came first, material well-being second, emotional well-being ranked third, and emotional well-being came in last place. In general, the quality of family life was average. The results also showed that psychological stress was moderate. There was no statistically significant relationship between the quality of family life and psychological stress. The results also maintained that there were no statistically significant differences in the quality of family life for participants due to sex of guardian, education level of the parents, or income.